ANALISIS KOMPETENSI PEGAWAI KOMISI PEMILIHAN UMUM KABUPATEN SUMEDANG - irma dewi agustin; Atang Harnata; Cucu Karya; Koswara; Popy Andyani; Shella Siti Sholihat (JRPA - Journal of Regional Public Administration, 2023)
Employee competence plays an important role in determining performance levels. Some indicators of competence include knowledge, skills and attitudes. An employee who has adequate knowledge and skills can help complete the work and tasks assigned to him, so success is highly dependent on this knowledge and skills. Besides knowledge and skills, attitude is also an indicator that determines the success of employees in carrying out their duties. This attitude is about how an employee faces work and interacts with coworkers. In this study, researchers used the competency theory according to Spencer and Spencer (Sutrisno, 2017) to measure the competency level of Sumedang Regency General Election Commission employees consisting of motives, traits, self-concepts, knowledge, and skills. The sampling technique used to determine research informants used purposive sampling so that the number of informants in this study was 3 people who were employees of the legal and human resources fields at the Sumedang Regency General Election Commission Office. data collection was carried out through field studies and literature studies, then the data was analyzed using data reduction methods, data presentation, conclusion drawing, and triangulation. the results showed that the level of competence of Sumedang Regency General Election Commission employees was said to be quite good. Employees are able to work according to their main duties and functions and can comply with applicable regulations, but not all employees have been given the opportunity to attend training so that the increase in employee knowledge of their work is uneven.